2006
DOI: 10.1002/jor.20117
|View full text |Cite
|
Sign up to set email alerts
|

Histological and scanning electron microscopy analyses of bone/implant interface using the novel Bonelike® synthetic bone graft

Abstract: Synthetic bone grafts provide an alternative to autografts and allografts. Bonelike 1 is a patented synthetic bone graft that mimics the mineral composition of bone. The aim of the present work was to assess the biological behavior of Bonelike 1 graft in humans, before using the material in orthopedic applications of bone regeneration, for example, in opening wedge high tibial osteotomies for medial knee osteoarthritis. Bonelike 1 granules were implanted in cortical bone of 11 patients undergoing osteotomies, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 29 publications
2
9
0
1
Order By: Relevance
“…All result of this study showed a pattern of bone formation in WPC similar to the result of other studies testing many grafts [36,37] . This pattern of bone formation which start from the wall of the bone defect toward the center, suggests that the WPC material is biocompatible and osteoconductive.…”
Section: Discussionsupporting
confidence: 89%
“…All result of this study showed a pattern of bone formation in WPC similar to the result of other studies testing many grafts [36,37] . This pattern of bone formation which start from the wall of the bone defect toward the center, suggests that the WPC material is biocompatible and osteoconductive.…”
Section: Discussionsupporting
confidence: 89%
“…1), and the ongoing release/deposition events of Ca and P ionic species leads to the rapid formation of an apatite layer, according to previous studies [39]. This behavior appears to contribute to the improved biological performance of Bonelike Ò , both in vitro [40,41] and in vivo [22,42,43]. In comparison, formation of an apatite layer on the surface of HA occurs slowly [39], with favorable surface conditions for cell growth being observed later.…”
Section: Discussionsupporting
confidence: 68%
“…73,74 Furthermore, the presence of glass in this formulation allows the introduction of several ions into BL composition, such as magnesium, fluoride, and sodium, making it possible to achieve a chemical composition closer to the mineral phase of the bone. [76][77][78][79] However, clinical applications were often performed using autologous blood as a carrier for the granules, which raises the need for a more adequate and less invasive vehicle to better stabilize the granules in large defects or unstable sites, avoiding dispersion or medullar infiltration. [76][77][78][79] However, clinical applications were often performed using autologous blood as a carrier for the granules, which raises the need for a more adequate and less invasive vehicle to better stabilize the granules in large defects or unstable sites, avoiding dispersion or medullar infiltration.…”
Section: Discussionmentioning
confidence: 99%
“…75 Clinical trials revealed its remarkable potential of osteoconductivity and osseointegration on orthopedic and dental applications. [76][77][78][79] However, clinical applications were often performed using autologous blood as a carrier for the granules, which raises the need for a more adequate and less invasive vehicle to better stabilize the granules in large defects or unstable sites, avoiding dispersion or medullar infiltration. Moreover, the development of a moldable/injectable formulation will increase the diversity of clinical cases in which BL can be applied.…”
Section: Discussionmentioning
confidence: 99%